Chemical Characterization and Insecticidal Properties of Essential Oils from Different Wild Populations of Mentha suaveolens subsp. timija (Briq.) Harley from Morocco. Issue 5 (May 2015) - Kasrati, Ayoub; Alaoui Jamali, Chaima; Bekkouche, Khalid; Spooner‐Hart, Robert; Leach, David; Abbad, Abdelaziz
Abstract The present study is the first investigation of the volatile‐oil variability and insecticidal properties of the endemic Moroccan mint Mentha suaveolens subsp. timija (mint timija). The yield of essential oils (EOs) obtained from different wild mint timija populations ranged from 0.20±0.02 to 1.17±0.25% (v/w). GC/MS Analysis revealed the presence of 44 oil constituents, comprising 97.3–99.9% of the total oil compositions. The main constituents were found to be menthone (1.2–62.6%), pulegone (0.8–26.6%), cis‐piperitone epoxide (2.9–25.5%), piperitone (0.3–35.5%), trans‐piperitone epoxide (8.1–15.7%), piperitenone (0.2–9.6%), piperitenone oxide (0.5–28.6%), (E)‐caryophyllene (1.5–11.0%), germacrene D (1.0–15.7%), isomenthone (0.3–7.7%), and borneol (0.2–7.3%). Hierarchical‐cluster analysis allowed the classification of the EOs of the different mint timija populations into four main groups according to the contents of their major components. This variability within the species showed to be linked to the altitude variation of the mint timija growing sites. The results of the insecticidal tests showed that all samples exhibited interesting activity against adults of Tribolium castaneum, but with different degrees. The highest toxicity was observed for the EOs belonging to Group IV, which were rich in menthone and pulegone, with LC50 and LC90 values of 19.0–23.4 and 54.9–58.0 μl/l air in the fumigation assay and LC50 and LC90 values of 0.17–0.18 and 0.40–0.52 μl/cm2 in the contact assay.